Training on making Pidada syrup and jam for the people of Roda Village, South Konawe - Agusrinal Agusrinal; Ismi Fadjriah Hamzah; Samsi Burhan; Armadi Chairunnas; Aqmal Khaery; Wandy Murti Prasetya; La Ode Ismail; Syahruddin Syahruddin; Habil Hamid; Murni Murni (Universitas Muhammadiyah Magelang, 2023)
Roda Village, which is located on the coast of Moramo Bay, has a fairly extensive mangrove area, most of which have been converted into shrimp and milkfish ponds. Converting mangrove land into ponds is quite dangerous if not balanced with land restoration efforts. One type of mangrove that is abundant on the coast of Roda Village is pidada (Sonneratia caseolaris). This activity aims to provide education to the public about the role and utilization of mangrove plants and processing pidada fruit into syrup and jam so that it can become an alternative livelihood. This activity uses the Participatory Rural Appraisal (PRA) approach to involve the active role of the community in implementing the activity. The result of this activity is that the people of Roda Village can understand the role and utilization of mangrove plants. In addition, the people of Roda Village can process Pidada fruit into syrup and jam.